Developing a monitoring and control system model for assessing performance of small scale gold mining production systems in the Philippines - Abeto, Paul Eric G. (2010)
The Philippines is one of the top producers of gold in the world. Artisanal gold mining in the Philippines is one of the metal industries that supply at least Php20 billion of the country'sGDP with thousands of people relying on the industry as their source of income. However, small-scale gold mining in the country is fairly an informal industry with minimal standards aside from the basic ones. To facilitate compettitiveness and sustainability, proper legislation and control of the industry must be present. The study developed a standard framework that would aid the mining companies and the governement mining regulatory agencies in assessing their performance such as in the environmental, economic, and operational aspects of small-scale gold mining facilities.